EVALUASI EFEKTIVITAS SISTEM PERINGATAN DINI SIKLON TROPIS DI INDONESIA : (Studi Kasus Siklon Tropis Seroja) - kiki, kiki; Salim Nur, Agus; Abubakar, Idhan (Jurnal Widya Climago, 2024)
A tropical cyclone is an atmospheric low pressure system in the tropics region that forms through convection over warm waters. The impacts of tropical cyclones include high intensity rain, strong winds, high waves, and storm surge, which can cause economic losses, environmental damage, and even loss of life. This study aims to evaluate the effectiveness of tropical cyclone early warning system in Indonesia, using Seroja tropical cyclone as a case study. The research method involved a field survey in the East Nusa Tenggara (NTT) region using a questionnaire designed based on the World Meteorological Organization (WMO) TCP-24 guidance document. The results showed that the current tropical cyclone early warning system is still ineffective. It is hoped that the findings of this study can provide information on the level of understanding and response of the community, and help improve the tropical cyclone early warning system in Indonesia.